Cybersex Behavior in Millenial Generation - Juditha, Christiany (Jurnal Pekommas, 2020)
One of the phenomena in modern society now because of the increasing use of internet is cybersex. The negative effects of cybersex are prostitution, cyber crime, child abuse and pornography. As the most accessed generation of the internet allows millennials to get involved in cybersex activity. The purpose of this study, therefore, is to get an idea of the current millennial-generation cybersex behavior. The research used survey method with quantitative approach. The results concluded that most of the respondents performed offline sexual activity (masturbation, sex, and oral sex) during the last 6 months. It was also revealed that most respondents had sex offline with boyfriends, close friends, strangers without marriage bonds. As for cybersex activity, most respondents do it everyday as much as one to two times a week at home. The purpose of doing cybersex is mostly out of curiosity, as entertainment and recreation. Most respondents in doing cybersex activity by porn sites, the rest to have sex conversations (sex chatting), download pornography and access multimedia/software sex. Other findings say respondents also confessed to having sex conversations with boyfriends, spouses, close friends and new people and meeting face-to-face with someone who previously only met online for sexual purposes.